Pendidikan Islam: Antara Realitas dan Cita-Cita - Zainuddin Zainuddin (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2020)
Abstract: Al-Quran is the highest guidance and direction for humans in carrying out life in the world and preparing for the afterlife. There are three basic teachings in the Qur'an, namely I 'iqqadiyah (related to faith), Khuluqiyah (virtue of character) and amaliyah (this relates to what comes from words and deeds). On the other hand, Islam was revealed in the Arabian Peninsula which was bound by mental aridity, spiritual misery, intellectual disturbances, polytheistic worship (watsaniyah) and human castration. Religious teachings before Islam were ignored, but gradually the Kuffar Quraysh finally accepted this new religion (Islam) with full awareness and confidence in a relatively short time. That means that they shouted and made the Qur'an as their guide in their lives. They are the most prominent guardians and spreaders in preserving and expanding Islam.